Pola Mata Pencaharian Tradisional dalam Masyarakat Kajang Studi Etnografi tentang Kesejahteraan Ekonomi - Haniifah Nabilah (IAIN Parepare, 2025)
This research aims to identify and analyze the traditional livelihood patterns of the Kajang community in relation to the concept of local wisdom-based economic welfare. The Kajang people, particularly the Ammatoa group, are known for their consistency in maintaining customary values that influence their economic, social and ecological systems. Using an ethnography-based qualitative approach, this study describes economic practices based on agriculture, forest products, and handicrafts, as well as the principle of simple living (kamase-mase) that is the foundation of collective welfare. The results show that these livelihood patterns serve not only as a survival strategy, but also as a form of resistance to modernization that potentially threatens local social and ecological structures. The findings make an important contribution to understanding traditional economic systems as contextualized models of sustainable development rooted in the culture of local communities.